Determination and Measurement of Post Advertising Effectiveness in Instagram Using Cri Method - Hermawan Junianto Irsan; Peni Sawitri (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
This study aims to analyze the effect of advertising attractiveness, the quality of advertising messages and advertising creativity on the effectiveness of Jenius’s advertising and to analyze the measurement of the effectiveness of advertising posts on Instagram using the Customer Response Index (CRI) method.The method of analysis in this study uses qualitative primary data, the test stages carried out are: validity, reliability, normality, heteroscedasticity, multiple linear regression, Customer Response Index (CRI), t test and coefficient of determination. The results showed that the advertising attractiveness variables, the quality of advertising messages and Jenius advertising creativity had a significant effect on the effectiveness of posting advertisements on Instagram, meanwhile the advertising creativity variable having a very large influence with t count 4.047. The measurement using the customer response index (CRI) method on the effectiveness of Jenius post ads on Instagram has an effectiveness of 89.39%.